Normal pregnancy and successful delivery in myophosphorylase deficiency (McArdle's disease). Issue 2 (April 1973) - Cochrane, Peter; Alderman, Brian
Abstract : The progress in pregnancy of a female with myophosphorylase deficiency (McArdle's disease) is described. In spite of the increased muscular effort expended, both pregnancy and labour were normal and the muscle symptoms unchanged, suggesting that compensatory mechanisms might have operated. These possible mechanisms are discussed. Women suffering from the myopathy need not expect any deterioration during pregnancy.